2020
DOI: 10.3390/atmos11040402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Reanalysis Datasets against Radiosonde over Southwest Asia

Abstract: Upper-air observational networks in Southwest Asia (SWA) are geographically sparse and reanalysis datasets (RDs) are a typical alternative. However, RDs can perform with varying degrees of quality and accuracy due to differences in assimilation schemes and input observations, among other factors. Geopotential height (gph), air temperature (tmp) and horizontal wind (U and V) modelled by the Japanese 55-year Reanalysis (JRA-55), the European Centre for Medium-Range Weather Forecasts Reanalysis Interim (ERA-I), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…While all datasets give a realistic representation of the major characteristics of the temperature structure within the TTL, ERA‐5 and CFSR are the best performing. However, Alghamdi (2020), and in a comparison between radiosonde measurements and reanalyses data over southwestern Asia, found that ERA‐5 is the worst performing of the four considered, with ERA‐Interim giving the best scores. In summary, while ERA‐5 has been found to outperform the other reanalysis products for several meteorological applications, it may not necessarily be the best performing in the Middle East.…”
Section: Model Set‐up and Datasetsmentioning
confidence: 99%
“…While all datasets give a realistic representation of the major characteristics of the temperature structure within the TTL, ERA‐5 and CFSR are the best performing. However, Alghamdi (2020), and in a comparison between radiosonde measurements and reanalyses data over southwestern Asia, found that ERA‐5 is the worst performing of the four considered, with ERA‐Interim giving the best scores. In summary, while ERA‐5 has been found to outperform the other reanalysis products for several meteorological applications, it may not necessarily be the best performing in the Middle East.…”
Section: Model Set‐up and Datasetsmentioning
confidence: 99%
“…A valuable alternative solution to observational datasets is atmospheric reanalysis data (Baatz et al, 2021), which combines vast amounts of observations with numerical models using data assimilation techniques to provide a globally complete gridded and continuous temporal coverage dataset. However, the accuracy of reanalysis products varies strongly (Dee et al, 2011) especially for variables that are very sensitive to atmospheric dynamics and to the main parameters of the assimilation systems, such as the quantity and quality of the assimilated observations, the assimilation scheme (e.g., variational, Kalman filter), and the background forecast model, particularly the spatial and temporal resolutions (Simmons et al, 2004;Alghamdi, 2020;Gleixner et al, 2020). The usability of reanalyses data for long-term climate applications, including trend estimation, is controversial as discussed in the literature, for specific regions in previous reanalyses generations (e.g., Thorne, 2008;Thorne and Vose, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out, comprehensive inter-comparisons between the old and new generations of reanalyses are provided in the literature. However, among the recent generations, the products' quality and suitability for a broad set of climate studies or applications are still under discussion or a few discussed for specific regions (e.g., Graham et al, 2019;Alghamdi, 2020;Keller and Wahl, 2021;Simmons, 2022). Furthermore, ERA5, the newest global reanalysis product and one of the most used reanalysis families, has not been extensively intercompared and discussed at the current time compared to the other products.…”
Section: Introductionmentioning
confidence: 99%
“…2009;Mao et al 2010;Marques et al 2010;Mooney et al 2011;Alfred et al 2011;You et al 2011You et al , 2013Cornes and Jones. 2013;Chen et al 2014;Taguchi et al 2017;Zhu et al 2017;He et al 2018;Alghamdi. 2020).…”
Section: Introductionunclassified